Regulation of alternative splicing in response to temperature variation in plants. (24th May 2021) - John, Sheeba; Olas, Justyna Jadwiga; Mueller-Roeber, Bernd
Abstract : Alternative splicing leads to diverse mature RNAs from a given gene. Here, we review current knowledge of alternative splicing triggered by a variation in environmental temperature in plants. Abstract: Plants have evolved numerous molecular strategies to cope with perturbations in environmental temperature, and to adjust growth and physiology to limit the negative effects of extreme temperature. One of the strategies involves alternative splicing of primary transcripts to encode alternative protein products or transcript variants destined for degradation by nonsense-mediated decay. Here, we review how changes in environmental temperature—cold, heat, and moderate alterations in temperature—affect alternative splicing in plants, including crops. We present examples of the mode of action of various temperature-induced splice variants and discuss how these alternative splicing events enable favourable plant responses to altered temperatures. Finally, we point out unanswered questions that should be addressed to fully utilize the endogenous mechanisms in plants to adjust their growth to environmental temperature. We also indicate how this knowledge might be used to enhance crop productivity in the future.